2006
DOI: 10.1111/j.1600-0579.2006.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tutorial input in addition to augmented feedback on manual dexterity training and its retention

Abstract: Virtual reality (VR) simulators can be used as tools in manual dexterity training. The visual feedback guides the subject towards proper performance but creates, at the same time, some dependency on this feedback. To overcome this drawback, the effect of adjunct tutorial input on motor learning behaviour was examined. Novice dental students were randomly assigned to one of two training groups or to a non-training control group, given the task of preparing a geometrical class 1 cavity in phantom teeth. The feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 15 publications
2
62
0
Order By: Relevance
“…This result was in agreement with our previous findings. Wierinck et al 6,7 found that floor smoothness' performance was enhanced by a fluent preparation technique and a reduced preparation time, a typical control group's strategy. More importantly, reducing the relative frequency of feedback during acquisition produced no differential effects on retention testing.…”
Section: Discussionmentioning
confidence: 98%
“…This result was in agreement with our previous findings. Wierinck et al 6,7 found that floor smoothness' performance was enhanced by a fluent preparation technique and a reduced preparation time, a typical control group's strategy. More importantly, reducing the relative frequency of feedback during acquisition produced no differential effects on retention testing.…”
Section: Discussionmentioning
confidence: 98%
“…This varies from the use of the traditional bench top exercises including manikins to high-technology devices, such as virtual reality simulators;15,16 however, these tasks require the integration of their theoretical knowledge. Some argued that in as much as tests for noncognitive psychomotor skills are not used during dental school admission procedures; schools must depend on application information consisting of predental grade point averages and the battery of dental admission tests 12,18…”
Section: Discussionmentioning
confidence: 99%
“…These projects vary from the use of traditional bench top exercises including dental phantom lab manikins to highly sophisticated devices, such as the virtual reality simulators 15,16…”
Section: Introductionmentioning
confidence: 99%
“…Implantology courses which have been established at many centers successfully are based on training models using either virtual reality models or models consisting of synthetic material or animal models like pig mandibula 12 or sheep corpses 4,7,13–15 …”
Section: Discussionmentioning
confidence: 99%